Clinical presentation and outcome of tuberculosis in chronic kidney disease stage 4 & 5 from a high TB burden country. - Sunil Kumar Dodani; Zaheer Udin Babar; Khadija Gul Mohammad; Saima Ali; Maryam Mushtaq; Salma Batool; Ali Nadeem; Asma Nasim (PLoS ONE)
Background Diagnosis and management of Tuberculosis (TB) in chronic kidney disease (CKD) is challenging. Our aim is to study clinical presentation and outcome in patients with stage 4 & 5 CKD from a high TB burden country. Methods All patients registered in Provincial TB Centre in tertiary care hospital in Pakistan from May 2016 to June 2020 were included. TB cases tested rifampicin resistant (RR) in GeneXpert were excluded from the study. Patients with CKD stage 4 & 5 were studied for demographics, TB history, clinical feature, diagnoses, treatment success and mortality. CKD stage 4 & 5 were compared with other patients registered at the TB treatment center. Results Out of 828, 259 (31%) had CKD stage 4 & 5. Out of 259, 156 (60%) had extra-pulmonary TB (EPTB). Microbiological diagnosis done in 118 (45.51%), 25% in EPTB and 72.9% in pulmonary TB (PTB). TB culture was positive in 46 (17.8%), Isoniazid resistance 21.7%. Treatment success was 80.7%. PTB was significantly associated with mortality (p = 0.031). In CKD stage 4 & 5 treatment success was significantly lower with high mortality (p = 0.033). Conclusion In CKD stage 4 & 5, EPTB is the most common presentation. Microbiological diagnosis could be achieved in one fourth of EPTB. There is high INH resistance. The treatment success is low with high mortality and PTB is a significant risk factor for mortality.